The political economy of military coup in Guinea: lessons for African states (2010)
The paper explores political issues in the context of Africa’s generally poor economic performance. With the coup in Guinea following the death of Lansana Conte, it is very clear that a mere transition to democratic governance is no guarantee that military coups will not occur in Africa. Although a military coup is regrettable and unacceptable, equally regrettable is the fact that coup offered an oppressed people the only platform for change and liberation as the democratic door has been shut. Since independence, African states have still not taken off economically. This has been attributed to corruption, repressive and personal rule of African leaders. The consequences have been political instability, poverty, diseases and underdevelopment. As a result, one way to reflect upon the recent coup in Guinea is to critically analyse how political and economic situations express and contribute to such phenomenon. However, Guinea represents a microcosm of Africa. The paper concludes that the only way to prevent coup as a recurring decimal in Africa is for African leaders to strengthen democracy and economic policies within the context of good governance, accountability and transparency